Ship resistance and propulsion practical estimation of ship propulsive power - Molland, Anthony F.; Turnock, Stephen R.; Hudson, Dominic A. (Cambridge University Press, 2017)
This second edition provides a comprehensive and scientific approach to evaluating ship resistance and propulsion. Written by experts in the field, it includes the latest developments in CFD, experimental techniques, and guidance for the practical estimation of ship propulsive power. It addresses the increasing emphasis on improving energy efficiency and reducing emissions, including the introduction of the Energy Efficiency Design Index (EEDI). The text also includes sufficient published standard series data for hull resistance and propeller performance to enable practitioners to make ship power predictions based on material and data within the book, and numerous fully worked examples illustrate applications for cargo and container ships, tankers, bulk carriers, ferries, warships, work boats, planing craft, yachts, hydrofoils, submarines and AUVs. The book is ideal for practicing naval architects and marine engineers, sea-going officers, small craft designers, undergraduate and postgraduate students, and professionals in transportation, transport efficiency and eco-logistics.